2020
DOI: 10.1111/ajr.12672
|View full text |Cite
|
Sign up to set email alerts
|

Remote health service vulnerabilities and responses to the COVID‐19 pandemic

Abstract: The rapid response to the COVID-19 pandemic in Australia has highlighted the vulnerabilities of remote Aboriginal and Torres Strait Islander communities in terms of the high prevalence of complex chronic disease and socioeconomic factors such as limited housing availability and overcrowding. The response has also illustrated the capability of Aboriginal and Torres Strait Islander leaders and the Aboriginal Community Controlled Health Services Sector, working with the government, to rapidly and effectively miti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 10 publications
0
46
2
1
Order By: Relevance
“…Telenursing provides access to health services, which can affect the condition of remote patients. 18 Nursing services performed in telenursing include patient triage, symptom management, education and control of using care tools such as oxygen capsules and masks through telephone and at home. 19–22 Counselling, education, diagnosis and record of patients' information are also possible through telenursing.…”
Section: Introductionmentioning
confidence: 99%
“…Telenursing provides access to health services, which can affect the condition of remote patients. 18 Nursing services performed in telenursing include patient triage, symptom management, education and control of using care tools such as oxygen capsules and masks through telephone and at home. 19–22 Counselling, education, diagnosis and record of patients' information are also possible through telenursing.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the usual gap between First Nations health and the general population has been reversed precisely because the response started with listening to communities and handing over control of the response (Silva, 2020). The challenge now for public health and policy is to build on this early success and address the longstanding structural vulnerabilities for these communities (Fitts et al, 2020).…”
Section: Collaborating As a Critical Friendmentioning
confidence: 99%
“…Similar to Canada, Australia has a vast expanse of land making it difficult to recruit health professionals in remote areas [ 7 ]. Researchers in Australia have found that individuals living in remote areas, including Indigenous communities, are made vulnerable to COVID-19 due to geographical and historical factors; as a result, they face higher rates of chronic disease and other socio-economic factors such as overcrowding, making compliance with social distancing guidelines difficult [ 8 ]. Residents of Indigenous communities in northern Canada experience similar vulnerabilities [ 9 ] as Indigenous peoples in Australia.…”
Section: Introductionmentioning
confidence: 99%
“…Commonly reported barriers to offering services via telehealth or online include concerns regarding privacy and safety, impact on rapport building between provider and clients, reduced non-verbal communication (gestures), and insufficient technological support [ 5 , 28 ]. In an Australian study in which researchers examined the impacts of COVID-19 on Aboriginal peoples and Torres Strait Islanders, these populations were found to experience a higher prevalence of chronic diseases and tobacco use but were also affected by socio-economic factors such as overcrowding, rendering Indigenous populations particularly vulnerable to COVID-19 [ 8 ]. In addition to the existing challenges that residents of remote communities face in accessing and receiving care in Australia, additional workforce challenges have also been noted during the pandemic such as changes in national demand for short-term work force and increased risk of losing permanent staff due to burnout [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation